Working Memory Load Attenuates Emotional Enhancement in Recognition Memory - Miendlarzewska, Ewa A.; Van Elswijk, Gijs; Cannistraci, Carlo V.; van Ee, Raymond (Frontiers in Psychology, 2013)
Emotionally arousing stimuli are perceived and remembered better than neutral stimuli. Under threat, this negativity bias is further increased. We investigated whether working memory load can attenuate incidental memory for emotional images. Two groups of participants performed the N-back task with two working memory load levels. In one group, we induced anxiety using a threat-of-shock paradigm to increase attentional processing of negative information. During task performance we incidentally and briefly flashed emotional distracter images which prolonged response times in both load conditions. A subsequent unannounced immediate recognition memory test revealed that when load at exposure had been low, recognition was better for negative items in both participant groups. This enhancement, however, was attenuated under high load, leaving performance on neutral items unchanged regardless of the threat-of-shock manipulation. We conclude that both in threat and in normal states working memory load at exposure can attenuate immediate emotional memory enhancement.